Evaluation of hemoglobin estimation with non-cyanide alkaline haematin D- 575 method - Anchinmane, Vyankatesh T.; Sankhe, Shilpa V. (International Journal of Research in Medical Sciences, 2016)
Background: Anemia is serious cause for concern in the world as it impacts on psychological and physical development, behavior and work performance. There are various methods recommended for estimation of hemoglobin for detection of anemia. Each method has its advantages and disadvantages. Aims and objectives of the present study were to compare conventional Hemoglobinocynide (HiCN) method containing potassium ferricyanide and potassium or sodium cyanide with non- cyanide alkaline haematin Method for hemoglobin estimation. Methods: The prospective study was conducted to evaluate the performance of two methods - HiCN method with Drabkin’s reagent and non- cyanide alkaline haematin method with AHD 575 reagent, for hemoglobin determination utilizing 201 blood samples. The data statistically analyzed by using coefficient of variation (CV), linear regression and mean differences. Results: A good correlation was observed for hemoglobin estimation between the HiCN method and non-cyanide alkaline haematin Method with AHD 575 reagent. The correlation coefficient of r= 0.9998 was statistically significant. Conclusions: It was concluded that both methods are accurate and precise, however the toxic and biohazardous effects of potassium ferricyanide and sodium cyanide in HiCN method can be prevented by using alkaline haematin method with AHD 575 reagent.